2008
DOI: 10.1542/peds.2007-3160
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Oral Health Training and Attitudes Toward Performing Oral Health Screenings Among Graduating Pediatric Residents

Abstract: Pediatric residents currently receive little training in oral health, and the majority wish for more. This study shows that oral health training during residency can increase pediatrician confidence in participating in important oral health promotion tasks, including anticipatory guidance, oral screenings, and oral health-risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
4
37
0
2
Order By: Relevance
“…Similar to the findings of the previous surveys done by Lewis et al (2009) andCaspary et al (2008), present study indicates that relatively low proportion of the paediatricians had received formal oral health education previously and many of the paediatricians are not feeling confident enough of having required capability for taking part in oral health care. In addition, consistent with previous studies, oral health training was found to be associated with improved oral health knowledge, confidence of entering oral health discussion with caregivers and identifying oral pathologies (Lewis et al, 2009;Douglass et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similar to the findings of the previous surveys done by Lewis et al (2009) andCaspary et al (2008), present study indicates that relatively low proportion of the paediatricians had received formal oral health education previously and many of the paediatricians are not feeling confident enough of having required capability for taking part in oral health care. In addition, consistent with previous studies, oral health training was found to be associated with improved oral health knowledge, confidence of entering oral health discussion with caregivers and identifying oral pathologies (Lewis et al, 2009;Douglass et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Initiation of tooth-brushing should start as early as when the first tooth erupts, on-demand breastfeeding could cause dental decay if required hygiene measures are not applied and first dental visit of a child to dentist should take place before 1 year of age (Public Health England, 2014b). While most respondents reported that they are willing to perform oral health promotion activities, lack of knowledge in these key areas and familiarity with dental related issues appears to be the most important barrier, similar to other studies (Caspary et al, 2008;Lewis et al, 2009), for paediatricians to be actively involved in oral health promotion in North Cyprus.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, pediatric care providers lack competence in performing oral health assessments and prevention services, and there is a need for additional oral health pedagogy in pediatric health professional education programs (Caspary, Krol, Boulter, Keels, & Romano-Clarke, 2008;Golinveaux et al, 2013).…”
Section: Introductionmentioning
confidence: 99%